The Impact of Contemporary and Multicultural Islamic Education Study on Postgraduate Students of IAIN Ponorogo - Wahyu Widodo; Syafitri Novita Wulandari; Salsabila Fatima; Sugiyar Sugiyar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Abstract The multiculturality of Indonesian society has positive and negative impacts on harmony between tribes, races, cultures and religions. Positive impacts on creating harmony, tolerance and the richness of the nation's culture. Negative impacts on claims on customs and conflicts if not managed properly. Like the conflicts that have occurred in Ambon, North Maluku, Poso and Central Kalimantan. This requires further review for the preventive mission of ethnic, racial, cultural and religious conflicts. The research aims to analyze the learning impact of contemporary and multicultural Islamic education studies on postgraduate students of IAIN Ponorogo. The research method was carried out using qualitative methods. Data collection was obtained through interviews, observation and documentation. The number of informants was 10 postgraduate students in the Islamic religious education study program for the 2022 academic year. Data analysis was carried out by data reduction, data presentation and drawing conclusions. The data presentation method used data display. The results showed that the study of contemporary and multicultural Islamic education at the IAIN Ponorogo postgraduate program had an impact on, (1) Increasing students' sensitivity to contemporary issues. Especially in understanding the culture that developed in modern times and the characteristics of modern society. (2) Students' understanding of the concept of multiculturalism, especially in addressing differences in race, ethnicity, culture, social strata, and religion, both on campus and in society.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//